TECHNOLOGY ADOPTION STRATEGY OF SOCIAL MEDIA IN MICRO SMALL MEDIUM ENTERPRISES - Nurqamarani, Adisthy Shabrina; Priyanto, Agus; Fadilla, Sarah (RJABM (Research Journal of Accounting and Business Management), 2022)
This study explores the I-T-O-E framework to understand the dominant factors that specifically influence MSME adoption. Micro, Small, and Medium Enterprises (MSMEs) as one of the most affected needs to implement a marketing strategy through social media, due to low costs and ease of reaching consumers on a wider scale. West Java was chosen as the research location because the level of technology adoption in MSMEs is the highest among other big cities. The culinary sector was chosen because it is one of the sectors most affected by the COVID-19 pandemic and is the sub-sector with the lowest use of internet media among other creative economy sub-sectors. The methodology is qualitative, involving interviews with participants (MSMEs in the culinary sub-sector) selected through snowball sampling.  The result shows that individual factor holds the most important role in determining social media strategy in MSME. This research is expected to have significant implications for both theory and state public policy in increasing digital interconnection, inclusivity, productivity, and MSME income.